Facing the sea challenges: swimming in 19th century Rio de Janeiro (1850's-1890's) - Melo, Victor Andrade de (Revista de História, 2015)
This study aims to discuss the conformation of the swimming practice in 19th century Rio de Janeiro, seeking to unveil its different facets, the various meanings attributed to it, considering that the subject could allow us to better understand some important dimensions of fluminense society in the period. To reach the goal, we used as sources newspapers and magazines published in the city, trying to understand the positions as representations that must be prospected in its materiality. We choose to investigate the 19th century (1850’s-1890’s) not only for being the moment in which the custom of swimming began to settle in the capital, but also due to the contextual framework, a period marked by changes in the city, including on adherence to ideas of modernity.